LIGHT CURVE TYPES OF CLASSIC T TAURI STARS - Ismailov, N. Z.; Adygezalzade, H. N. (Одеські астрономічні публікації, 2016)
By using the archive photometric data’s obtained for a long time intervals we have carried out a master light curves of 28 classical T Tauri type stars. For the physical character of variability mainly 5 type light curves can be separated. We have proposed a new scheme of classification among the examined light curves. The proposed scheme suggests a qualitative interpretation in terms of interaction of the central star with its circumstellar accretion disk.